Penyuluhan Pengembangan Program Cipta Reproduksi Sehat Sebagai Upaya Peningkatan Kualitas Remaja Sadar Kesehatan Reproduksi Di SMK Yappi Wonosari Kabupaten Gunungkidul - Tutik Astuti (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
YAPPI Wonosari Vocational School (STM) is a private vocational high school with A accreditation, having its address at Bansari, Kepek Wonosari, Gunungkidul. With a capacity of 20 classes, divided into class X, there are 8 classes; class XI, there are 8 classes; and class XII, there are 4 classes. The aim is to provide knowledge about the importance of adolescent reproductive health. The service method is provided by providing counseling to adolescents at the YAPPI Vocational School (STM) in Wonosari, Gunungkidul, regarding adolescent reproductive health. The results of the devotion before giving showed that the majority had less knowledge, namely 15 people, or 45.71%. After the counseling was carried out, knowledge was measured again, and it was proven that there was an increase in the number of 12 people, or 37.14%, having good knowledge. Knowledge is the result of knowing, and this occurs after someone makes observations of certain objects. Observation occurs through the five human senses, namely the senses of sight, hearing, smell, taste, and touch. Most of human knowledge is acquired through the eyes and ears, that is, through the process of seeing and hearing reality.